Implementasi Model Project Based Learning (PjBL) untuk Meningkatkan Keaktifan dan Hasil Belajar Siswa Pada Pembelajaran Matematika - Annissya Nuraini Rahmawati, Annissya Nuraini Rahmawati; Rosanawati, I Made Ratih; Sadino (Edudikara: Jurnal Pendidikan dan Pembelajaran, 2024)
This research aims to describe the planning, implementation, and evaluation of steps for implementing the Project Based Learning (PjBL) model in increasing activity and mathematics learning outcomes. This type of research is classroom action research (PTK), which is carried out in two cycles. This research was carried out at SDN Palur 02, with the research subjects being class 5A students, totaling 20 students. Data collection techniques use test techniques, while non-test data analysis techniques are descriptive, quantitative and qualitative. The research results show that by implementing the steps of the Project Based Learning model, it has succeeded in increasing student activity and learning outcomes. This is proven by the increase in student learning activity from pre-cycle conditions 38.34was in the less active category to 65.78 in cycle I. Cycle II showed that 82.08 students’ learning activeness had reached the active category. An increase also occurred in the mathematics learning outcomes of class 5A students at SDN Palur 02 for the 2023/2024 academic year after being given the Project Based Learning (PjBL) model action. Before the action was taken, 8 students (40%) received a complete score. After taking action in cycle I, there was an increase in the number of students who completed the program by 13 students (65%); in cycle II there was an increase in the number of completions to 16 (80%).